The Influence of Stress Perception on Academic Procrastination in Postgraduate Students: The Role of Self-Efficacy for Self-Regulated Learning and Self-Control - Yan Ma; Xi Mei Yang; Lan Hong; Ren Ju Tang (International Journal of Digital Multimedia Broadcasting)
Academic procrastination is a common problem among current master’s degree students in their research activities and is an important factor that hinders academic progress. Based on the cognitive theory perspective, this study conducted a web-based questionnaire survey on full-time master’s students enrolled in a teacher training university in southwest China. The data collected were analyzed by using SPSS software with hierarchical regression and PROCESS macroprogramming techniques to investigate the relationship between stress perception and academic procrastination and the moderating effects of self-regulated learning efficacy and self-control among master’s students. The study showed that stress perception was a significant positive predictor of academic procrastination, and both self-regulated learning efficacy and self-control played a moderating role in the relationship between stress perception and academic procrastination. The study suggests that, firstly, to stimulate the personal potential of graduate students with reasonable perception of stress; secondly, to enhance the action ability of graduate students by strengthening metacognitive strategies; finally, to establish a two-way promotion mechanism by enhancing self-regulation and impulse control.